Keanekaragaman Plankton di Sungai Komering Desa Serdang Menang Kecamatan Sirah Pulau Padang Kabupaten OKI - Muhammad Taufan Febrianto; Indah Anggraini Yusanti; Syaeful Anwar (Universitas PGRI Palembang, 2020)
The purpose of this study was to determine the diversity index of plankton in the Komering River Serdang Menang Village, Sirah Pulau Padang District, Ogan Komering Ilir Regency.Â This research was conducted in March until April 2018 in the Komering River in Serdang Menang Village, Sirah Pulau Padang District, Ogan Komering Ilir Regency. Sampling method uses Purposive Random Sampling which consists of 3 observation stations, namely: station 1 sand mining area, station 2 floating net cage fish farming area and station 3 densely populated area. The results of the study found that the composition of plankton in the Komering River in Serdang Menang Village, Subdistrict of Sirah Pulau Padang in Ogan Komering Ilir Regency consisted of 3 phytoplankton classes, namely Bacillariophyceae, Chlorophyceae and Cyanophyceae, while the zooplankton class consisted of 4 classes, namely Mastigophora, Monogononta, Crustacea and Ciliophora. The highest diversity index for phytoplankton was obtained at stasion 1 in the sand mining area with a value of 1,39, which indicates that the level of diversity is included in the mediun category. At zooplankton the highest diversity indev was found at station 3 with a value of 0,33 which indicates that the level of diversity is included in the low category. While the highest dominace index in phytoplankton was found in station 3 in densely populated areas with a value of 0,43 while in zooplankton it was found in stasion 1 in the sand mining area with a value of 0,00563, both value indicate that there is no genus of plankton that dominates in the area.